A new species of Aricoris Westwood, [1851] belonging to “chilensis” group (Lepidoptera: Riodinidae) - Siewert, Ricardo Russo; Dolibaina, Diego Rodrigo; Mielke, Olaf Hermann Hendrik; Casagrande, Mirna Martins; Moser, Alfred (Zootaxa, 2014)
A new species of Riodinidae from the grasslands of South Brazil, Paraguay and Argentina, Aricoris schneideri sp. nov., is described.